A Guide to Responsible Scaring: What are the Limitations of Horror in Young Adult Fiction? - Dan Hunt (Leaf Journal)
Through a close reading of recent Young Adult (YA) horror novels – including Clown in a Cornfield by Adam Cesare; Harrow Lake by Kat Ellis; and I Feed Her to the Beast and the Beast is Me by Jamison Shea – as well as Dan Hunt’s own work-in-progress, this article explores the building blocks of the YA horror genre. It explores how YA horror adapts and challenges traditional genre limitations to suit a younger audience, investigating the boundaries of fear in YA fiction by asking: how scary is too scary? The article argues that hesitations toward writing YA horror fiction stem from a misconception that the genre is bound by restrictive rules, leading to diluted narratives. However, this perception often arises from a lack of research and understanding. To challenge these misconceptions, the article offers a framework for “responsible scaring” in YA horror writing.